Association between magnesium status, oxidative stress and inflammation in preeclampsia: A case–control study. Issue 6 (December 2015) - de Sousa Rocha, Vivianne; Della Rosa, Fernanda Brunacci; Ruano, Rodrigo; Zugaib, Marcelo; Colli, Célia
Summary: Background & aims: Preeclampsia is responsible for more than one-third of all maternal deaths in Brazil. The objectives of the present study were to evaluate magnesium status and its association with oxidative stress and inflammation in preeclamptic women, and to identify the predictor variables of the disorder. Methods: The study population consisted of 36 women divided into preeclamptic ( n = 18) and control groups ( n = 18). The preeclamptic group included women (≥20 weeks of pregnancy) with arterial pressure ≥ 140/90 mmHg and proteinuria >0.3 g/24 h, while the control group comprised pregnant women with no clinical/obstetric complications. Magnesium intake was assessed via a food frequency questionnaire validated for pregnant women in Brazil. Plasma, erythrocyte and urinary magnesium levels were determined by flame atomic absorption spectroscopy, while oxidative stress and inflammatory markers were assessed using standard protocols. Logistic regression analysis was used to identify the predictors of preeclampsia. Results: Preeclamptic and control groups were similar with respect to magnesium intake and urinary excretion, while plasma and erythrocyte magnesium concentrations were higher in the former group. Plasma magnesium was positively correlated with catalase and glutathione peroxidase activities and with concentrations of interleukin-6 and tumor necrosis factor alpha. Regression analysis showed that plasma magnesium and urinary 8-isoprostane were associated with preeclampsia. Conclusion: Magnesium status appears to result from homeostatic imbalance and physiological alterations typical of preeclampsia. Increased plasma magnesium and decreased urinary 8-isoprostane were considered predictors of preeclampsia.